Square Root Method Trinomial Method when a = 1 GCF 1A.4 Factoring Square Root Method Trinomial Method when a = 1 GCF
Solving with Square Roots Get x2 or the binomial squared by itself Take the square root of BOTH sides of the equal sign Don’t forget the sign Simplify
Solve by Taking Square Roots X = ± 2i
Solve by Taking Square Roots X = ± 3 2
Solve by Taking Square Roots X = ± 3
Solve by Taking Square Roots X = -4 ± 3 2
Solve by Taking Square Roots 5. 5(x – 4)2 = 125 X = -1 and 9
Solve by Taking Square Roots 6. - 3 5 x2 – 2 = -5 X = ± 5
Solve by Taking Square Roots 7. - 9x2 = 243 X = ± 3i 3
Solve by Factoring (a=1) Standard Form of a Quadratic Equation: ax2 + bx + c = 0 Put the equation in descending order from highest power to lowest power. List all the factors of c. Determine which factors of c when added together equal b. Create two binomials with the variable as the first term and set it equal to zero… (x )(x )= 0 Write in the factors that you determined from step 3. Set each binomial equal to zero and solve each one for your variable.
Solve by Factoring (a=1) 1. 8x + x2 + 7 = 0 x = -7 x = -1
Solve by Factoring (a=1) 4. x2 – x – 56 = 0 x = -7 x = 8
Solve by Factoring (a=1) 2. n2 – 11n + 10 = 0 n = 10 n = 1
Solve by Factoring (a=1) 3. m2 + m – 90 = 0 m = 9 m = -10
Solve by Factoring (a=1) 5. x2 – 5x – 104 = 0 x = -8 x = 13
Solve by Factoring When There is a Greatest Common Factor(GCF) Standard Form of a Quadratic Equation: ax2 + bx + c = 0 When a > 1, examine the factors of a, b and c to determine if there is a GCF (the largest number that a, b & c can all be divided by). Divide each term of the quadratic equation by the GCF. Put the GCF in front and the new trinomial from step 2 in parentheses, and set it equal to zero. Factor the trinomial like normal.
Solve by Factoring (GCF) 1. 2x2 + 6x – 108 = 0 x = -9 x = 6
Solve by Factoring (GCF) 2. 3x2 + 9x – 54 = 0 x = -6 x = 3